The Impact of Moral Learning on Students’ Morality at Islamic Junior High School Baiturrahman Teluk Kuantan - Afriandi, Budi; Hakim, Rosniati; AM, Rusydi; Syaifullah, Syaifullah; Kamal, Tamrin (Al-Hijr: Journal of Adulearn World, 2024)
Moral education has a significant role in shaping the noble character of students. Good morals reflect a noble personality and are the foundation for a dignified civilization. However, many students’ morals still do not follow what is expected in the field. Therefore, this research aims to find and analyze how Islamic Junior High School Baiturrahman Teluk Kuantan builds the noble character of students through moral education. The research method used by the author is a qualitative approach to deepen the understanding of noble character through moral education. These methods can involve interviews, observations, and documentation. Based on the results of the research show that Islamic Junior High School Baiturrahman Taluk Kuantan emphasizes the importance of moral education or character education in developing personality and noble character in students, which includes the development of positive qualities such as honesty, responsibility, respect, tolerance, kindness, and in the end can bring positive benefits to the Islamic Junior High School Baiturrahman extended family.